La gestion des afflux massifs de sargasses dans la grande Caraïbe : nouvel enjeu de la coopération régionale - Karine Galy (Études Caribéennes)
The massive influx of sargassum on the coasts of the countries and territories of the Greater Caribbean mobilise various actors (private, public, States, municipalities, associations ...) among which, regional organisations. Faced with the tangle of means and legal frameworks to deal with this new phenomenon, a skilful coordination between the different stakeholders is essential to avoid confusion and facilitate an effective intervention. Within the organisations of the area, solidarity to face sargassum, while forging a new object of cooperation, is proving to be a test of the multiple fragmentations that characterises the region.